Effect of Body Mass Index on Overall Survival of Pancreatic Cancer: A Meta-Analysis. Issue 14 (April 2016) - Shi, Yu-Qi; Yang, Jing; Du, Peng; Xu, Ting; Zhuang, Xiao-Hui; Shen, Jia-Qing; Xu, Chun-Fang
Abstract : Abstract: Although obesity has been identified as a risk factor for pancreatic cancer, the important question of whether obesity influences the prognosis of pancreatic cancer has not been explicated thoroughly. We therefore performed a meta-analysis to investigate the association between body mass index (BMI) and survival outcomes of patients with pancreatic cancer. Studies that described the relationship between BMI and overall survival (OS) of pancreatic cancer were searched in PubMed, Embase, Ovid, and Cochrane Library Databases from the earliest available date to May 12, 2015. Hazard ratios (HRs) for OS in each BMI category from individual studies were extracted and pooled by a random-effect model. Dose–response meta-analysis was also performed to estimate summary HR and 95% confidence interval (CI) for every 5-unit increment. Publication bias was evaluated by Begg funnel plot and Egger linear regression test. Ten relevant studies involving 6801 patients were finally included in the meta-analysis. Results showed that obesity in adulthood significantly shortened OS of pancreatic cancer patients (HR: 1.29, 95% CI: 1.17–1.41), whereas obesity at diagnosis was not associated with any increased risk of death (HR: 1.10, 95% CI: 0.78–1.42). For every 5-kg/m 2 increment in adult BMI, the summary HR was 1.11 (95% CI: 1.05–1.18) for death risk of pancreatic cancer. However, no dose–response relationship was found in the BMI at diagnosis. Egger regression test and Begg funnel plot both revealed no obvious risk of publication bias. In conclusion, increased adult BMI is associated with increased risk of death for pancreatic cancer patients, which suggested that obesity in adulthood may be an important prognostic factor that indicates an abbreviated survival from pancreatic cancer. More studies are needed to validate this finding, and the mechanism behind the observation should be evaluated in further studies.